The Effect of Corporate Social Responsibility on Organizational Effectiveness - Jerusha Angelene Christabel G; S. Suman Rajest; R. Regin (Central Asian Journal of Literature, Philosophy and Culture, 2022)
For decades, scholars and businesspeople have argued over CSR. A definition, history, and current application of CSR are outlined here. Scholarly work has contributed to the expansion of this concept, which originally posited that businesses should consider the interests of the government and other policymakers alongside those of their shareholders, employees, consumers, and communities. The article describes the reasons for and components of CSR, its scope, and current projects. The study delves into CSR’s history, worldwide necessity, and individual significance. All facets of the economy, society, and ecosystem will be examined. Workplace, market, community, and environmental aspects of CSR will be highlighted and analysed alongside their importance to the success of any business. Topics covered include corporate social responsibility, corporate volunteerism, cause marketing, cause-related marketing, and cause-related advertising. We’ll discuss how CSR helps businesses, communities, and the environment in developed and developing nations. The objectives, literature, and techniques of this study will be discussed. The theoretical part of the study defines CSR. In contrast, the experimental part examines the concept’s reception in a developing country and the private sector’s view of CSR’s efficacy as a social change agent. The research looks specifically at how financial institutions and large companies in the area implement CSR policies and programmes. Also explored is the degree to which corporations of varying sizes are prepared to implement CSR initiatives. In the end, the paper concludes that corporate owners should prioritise social good.